'Going far is returning': Dance Movement Psychotherapists find resilience and learning and call for more collaboration and dialogue. Issue 1 (1st July 2016) - Coaten, Richard; Williams, Sarah
Dance Movement Psychotherapy (DMP) can contribute more to the care of people with dementia, a subject of increasing interest and importance in the United Kingdom and globally. This article was first presented at the International Centre for Research in Arts Therapies Conference at Anglia Ruskin University, Cambridge. It contributes to growing knowledge in the field by discussing and analysing two different, yet complementary narratives about practice then and now: first, from the perspective and learning of someone just starting out in their career as a dance movement psychotherapist and second from one who started out using dance therapeutically in the mid-1980s. The outcomes of this dialogue have helped build resilience, have fostered dialogue and learning between practitioners, and are clinically relevant to students in training and experienced practitioners alike. Outcomes also shed light on transference and counter-transference, and make a call for more collaboration and communication between dance movement psychotherapists just starting out in their careers and those more experienced. Much can be learnt from more collaboration and dialogue between DMP's, dancers and other somatic practitioners working in the dementia care field.